Reflections on the infeasibility of labor demand as a guiding principle for university planning - Velázquez Fernández, Ángel Ramón (2017)
There is no doubt about the need for an appropriate balance between the levels of economic and social development. Both theoretical interpretations and practical experience confirm this assertion. Each step in economic development, each unit of growth in the Gross Domestic Product, opens up new possibilities for the full development of society, expanding the quality of life in all areas. At the same time, this social development constitutes a sine qua non condition for economic development.